Analysis of drug treatment outcome in clarithromycin-resistant Mycobacterium avium complex lung disease. Issue 1 (December 2015) - Kadota, Tsukasa; Matsui, Hirotoshi; Hirose, Takashi; Suzuki, Junko; Saito, Minako; Akaba, Tomohiro; Kobayashi, Kouichi; Akashi, Shunsuke; Kawashima, Masahiro; Tamura, Atsuhisa; Nagai, Hideaki; Akagawa, Shinobu; et al.
Abstract Background Although the isolation of clarithromycin (CAM)-resistant Mycobacterium avium complex (MAC) indicates a poor treatment outcome and increased mortality, there have been only a few reports on drug treatment for CAM-resistant MAC lung disease. We aimed to reveal the effectiveness of the continuation of a macrolide and the use of a multidrug regimen in the treatment of CAM-resistant MAC lung disease. Methods Among patients with MAC pulmonary disease as defined by the 2007 criteria of the American Thoracic Society and the Infectious Diseases Society of America statement, those with CAM-resistant MAC (minimum inhibitory concentration ≥32 μg/ml) isolated, newly diagnosed and treated from January 2009 to June 2013 were analysed in this study. Effectiveness was measured based on culture conversion rate and improvement of radiological findings. Results Thirty-three HIV-negative patients were analysed in this study. Twenty-six were treated with a regimen containing CAM or azithromycin (AZM), and 21 patients were treated with three or more drugs except macrolide. The median duration to be evaluated was 10.4 months after beginning the treatment regimen. Sputum conversion (including cases of inability to expectorate sputum) was achieved in 12 (36 %) patients. Radiological effectiveness improved in 4 (12 %) patients, was unchanged in 11 (33 %) patients and worsened in 18 (55 %) patients. In the multivariate analysis, CRP <1.0 mg/dl (p  = 0.017, odds ratio 12, 95 % confidence interval (CI) 1.6–95) was found to be the only significant risk factor for radiological non-deterioration, and no significant risk factors for microbiological improvement were found. Conclusions Our results suggested that continuation of macrolides or the addition of a new quinolone or injectable aminoglycoside to therapy with rifampicin and ethambutol would not improve clinical outcome after the emergence of CAM-resistant MAC. However, further prospective study is required to evaluate the precise clinical efficacy and effectiveness of these drugs.